2006
DOI: 10.1529/biophysj.106.080721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of MscL Interactions with a Curved Lipid Bilayer

Abstract: Mechanosensitivity is a ubiquitous sensory mechanism found in living organisms. The simplest known mechanotransducing mechanism is found in bacteria in the form of the mechanosensitive membrane channel of large conductance, MscL. This channel has been studied extensively using a variety of methods at a functional and structural level. The channel is gated by membrane tension in the lipid bilayer alone. It serves as a safety valve protecting bacterial cells against hypoosmotic shock. MscL of Escherichia coli em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(69 citation statements)
references
References 52 publications
1
68
0
Order By: Relevance
“…11 The S1 in the revised version has a helical structure running parallel to the cytoplasmic membrane surface instead of In order to examine the structural changes during the opening of MscL in atomic detail, molecular simulations, including all atom and coarse-grained models, have been conducted. [20][21][22][23][24][25][26][27][28] The first problem to simulate channel opening is how to apply forces to a modeled MscL. One method employed force tethered to particular AAs or whole-channel proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The S1 in the revised version has a helical structure running parallel to the cytoplasmic membrane surface instead of In order to examine the structural changes during the opening of MscL in atomic detail, molecular simulations, including all atom and coarse-grained models, have been conducted. [20][21][22][23][24][25][26][27][28] The first problem to simulate channel opening is how to apply forces to a modeled MscL. One method employed force tethered to particular AAs or whole-channel proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Another method is to generate stress in the MscL-embedded membrane by modifying the bilayer structure. 25,26 This method is based on the findings that pressure distribution in the membrane varies with the type of the membrane and that the pressure profile of the membrane affects the channel gating, 22 however, it could not induce MscL opening within the simulation period, 25 or only revealed that how MscL adapt to a thinner membrane. 26 Therefore, it is critically important to develop a stimulation method that can mimic the membrane stretching, which is used in most experiments to stimulate MscL.…”
Section: Introductionmentioning
confidence: 99%
“…Its function is also not known, although it has been proposed that the loop behaves as a molecular spring, resisting the channel opening (1). This notion has found support from results of mutagenesis (100), EPR spectroscopic (102,149), and MD studies (40,103). Nevertheless, further experimental and modeling studies are needed to fully establish the role of this structural domain of MscL.…”
Section: Structure Of Msclmentioning
confidence: 86%
“…The other global determinant, bilayer curvature and/or transbilayer pressure profile, has been established as the major factor regulating MscL and MscS structural conformations. With regard to specific interactions of the MscL and MscS structural components with surrounding phospholipids, several studies have suggested that the periplasmic and cytoplasmic regions are critical for these interactions (103,111,149,163,166).…”
Section: Mscl and Mscs As A Paradigm For Mechanosensory Transductionmentioning
confidence: 99%
See 1 more Smart Citation